Ethical Considerations of WhatsApp Usage among Jordanian University Students: A Case Study of Mass Communication Colleges - Al Olaimat , Farhan (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aimed to identify the ethical implications of using WhatsApp among Jordanian university students, as well as the gratifications derived from its usage.WhatsApp among Jordanian university students, as well as the gratifications derived from its usage. Methods: The study employed a descriptive research design and utilized the survey method. The study population comprised university students from media faculties, and a simple random sample of 322 individuals was drawn from the following universities: Yarmouk University, Petra University, and Zarqa National University. Results: The study yielded several key findings. Firstly, the primary motives for Jordanian university students' use of WhatsApp were identified as ritual purposes, entertainment, and social bonding. Regarding gratifications, the study revealed that the most prevalent were practical gratifications, particularly entertainment and a sense of happiness. Notably, 74.9% of the study sample showed little interest in the ethical considerations of using WhatsApp. Conclusions: Based on the findings, the study recommends the importance of adhering to communication ethics in general and social network ethics, specifically in the case of WhatsApp, as examined in this study.